Lareh Koto Piliang: Sistem Kekuasaan dan Musik Perunggu Dalam Kajian Konsep Estetika Musikal di Luhak Nan Tigo Mingkabau - Andar Indra Sastra (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2016)
This article aims to discover the concept of Lareh Kotopiliang: Power Systems and Bronze Music in a Study of the Concept of Musical Aesthetics in Luhak Nan Tigo Minangkabau. Lareh Kotopiliang is oriented towards a royal or autocratic system of power, in which the primary figure holds the title of Dt. Katumangguangan. A legendary figure, Dt. Katumangguangan is believed to be the one who first implemented this autocratic system of power or leadership. There are two types of bronze music, namely oguang and talempong. From the aspect of performance, there are two different concepts: (1) oguang (a gong ensemble); and (2) talempong bararak (processional music). As an ensemble, oguang is played on top of a frame (rea), with gandang palalu and paningkah, six talempong, and two gongs. Talempong bararak is performed in procession – in declaration of the title of a headman, and musically is made up of three pairs of talempong – talempong jantan, talempong paningkah, and talempong pangawinan. Each of the talempong pairs plays a different rhythmic pattern, and the combination of the three patterns forms the characteristic melody of talempong bararak. The problems addressed in this article are: first, the traditional historiography of Lareh Koto Piliang as part of the trilogy of power in Luhak Nan Tigo Minangkabau; second, Lareh Koto Piliang and the concept of bronze music; and third, the musical concept of talempong bararak.